Alterações bioquímicas e fisiológicas das sementes de Tabebuia roseoalba (Ridl.) Sandwith (Bignoniaceae) submetidas ao armazenamento - Abbade, Leticia Caravita; Takaki, Massanori [UNESP] (FapUNIFESP (SciELO), 2014)
Tabebuia roseoalba (Ridl.) Sandwith is a Brazilian forest species, with great use in landscaping and reforestation, occurring mainly in the semi-deciduous forest. Seeds are small, lightweight, winged and wind-dispersed. The objective of this study was to verify the physiological quality and biochemical changes in T. roseoalba seeds during 24-month storage. The following were assessed: germination, emergence, seedling length and seedling dry weight, content of lipids, proteins and phenolic compounds, and enzyme activity. Loss of seed quality during storage was evidenced by reduced germination and emergence, shorter seedling length and lower seedling dry weight, decreased content of lipids and proteins, decreased peroxidase and catalase activity, and increased phenolic compound content and polyphenol oxidase activity. Seeds should be stored and used within six months after collection.
Biochemical and physiological changes of Tabebuia roseoalba (Ridl.) sandwith (Bignoniaceae) seeds under storage
Keywords: Catalase; Emergence; Germination; Lipids; Peroxidase; Polyphenol oxidase